Front cover: Effects of a Grapevine Shoot Extract Containing Resveratrol and Resveratrol Oligomers on Intestinal Adenoma Development in Mice: In Vitro and In Vivo Studies. Issue 2 (22nd January 2018) - Empl, Michael T.; Cai, Hong; Wang, Shan; Junginger, Johannes; Kostka, Tina; Hewicker‐Trautwein, Marion; Brown, Karen; Gescher, Andreas J.; Steinberg, Pablo
Abstract : Mol. Nutr. Food Res. 2018, 62, 1700450 DOI:10.1002/mnfr.201700450 A grapevine shoot extract, which contains resveratrol as well as resveratrol oligomers, significantly reduces intestinal adenoma number in male Apc Min mice fed a high‐fat diet. In addition, the extract as well as some of its isolated ingredients inhibit the growth of adenoma‐derived APC10.1 cells in vitro by inducing cell cycle arrest, senescence, and apoptosis.